A field-scale evaluation of the removal of odorous gases by a plant material-based deodorant - Wu, Jun; Yang, Jing; Wang, Jian; Fang, Liben; Fang, Jingjing (Frontiers in Environmental Science, 2023)
The composting process emits various volatile chemicals, including hydrocarbons, nitrogen compounds, sulfur compounds, and oxygenated compounds. These gases must be removed to avoid atmospheric pollution. Spraying extracted materials from plants, such as tea tree oil, onto the surface of a windrow is a novel odor reduction technique for the treatment of gaseous emissions from composting facilities. In this study, a plant material-based deodorant from a mixture of coconut, lemon, and tea tree essential oils was sprayed directly onto the surface of a windrow with a spraying frequency of three times a day. Odorous compounds were measured before and after spraying to evaluate the performance of the plant material-based deodorant. After spraying, the ammonia concentration decreased from 10,000 to 7,000 μg/m3. There was a large decline in alcohols, aromatics, and carbonyls, from 3,0612, 12,270, and 5,138 μg/m3 to 4,965, 4,669, and 2,253 μg/m3, achieving efficiencies of 83%, 62%, and 56%, respectively. The removal efficiencies for terpenes, volatile fatty acids, sulfur compounds, and ammonia were lower than the former, falling within the range of 24–36%. Theoretica total odor concentration was decreased from 23,757 μg/m3 at the beginning to 13,056 μg/m3 in the end, revealing that most of the bad smell has been eliminated.